If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2x-5)-3(x+2)=5(2-x)
We move all terms to the left:
2(2x-5)-3(x+2)-(5(2-x))=0
We add all the numbers together, and all the variables
2(2x-5)-3(x+2)-(5(-1x+2))=0
We multiply parentheses
4x-3x-(5(-1x+2))-10-6=0
We calculate terms in parentheses: -(5(-1x+2)), so:We add all the numbers together, and all the variables
5(-1x+2)
We multiply parentheses
-5x+10
Back to the equation:
-(-5x+10)
x-(-5x+10)-16=0
We get rid of parentheses
x+5x-10-16=0
We add all the numbers together, and all the variables
6x-26=0
We move all terms containing x to the left, all other terms to the right
6x=26
x=26/6
x=4+1/3
| 3(x-1)-(x-9)+(x-3)=(x+4)+(x+2) | | 36-4x=18 | | 10n+n-35=£3.40 | | 109/y=18 | | -x2-8x+240=0 | | x-0.2x=63 | | 39x–5=7 | | -5t^2+20t+80=0 | | 1,5x+3(15-x)=36 | | 3/2z=8 | | F(x)=-8x-5 | | 6=6*x-3 | | (9x-)(5x+4)-(9x-1)(3x-1)=0 | | x1+x2=-2 | | x=x*3-5 | | 3x+12=2x–4 | | 100x1,2^x=150 | | (7x-1)(3x+2)=0 | | 14x-7=11x-1 | | 8x-36=9 | | x-45=62 | | 104,04+144=c2 | | F(10)=450-30x | | 0.5^x=50 | | x−194=−342 | | 54=40–6x | | 13-14=3t+16 | | (65+x)/2=70 | | x-53=1 | | 3/5=m/10 | | 5/n=30/36 | | Y=49+0.15x |